Food Availability and Stomach Content of Fish Populations in Semenyih Reservoir, Malaysia - Dizon Peralta, Eduardo (2004)
This study was done to evaluate the food availability and stomach content of fish populations in Semenyih Reservoir, Malaysia. Samples were collected at monthly intervals from November 1998 to October 1999. Fish specimens were collected from twelve stations at the shallow littoral zone of the reservoir using various sizes of gill nets for the investigation of fish species inhabiting the reservoir and for the examination of the gut content. A total of 1,469 fish were collected from the Reservoir throughout the study. Seven species belonging to seven different families were identified. Fish community consisted of Mystacoleocus marginatus C&V (sia), Hampala macrolepidota van Hasselt (sebarau) Cyclochelichthys apogon C&V (merah mata), Osteochilus hasselti C&V (terbul), Oreochromis mossambicus Peters (tilapia), Oxyleotris marmorafus Bleeker (Ketutu), and Mystus nemurus C&V (baung). Mystacoleocus marginatus was the most dominant species, comprising 64.6% of the total number of fish sampled, followed by H. macrolepidota (24.8%), C. apogon (4.2%), 0. hasseltii (2.6%), 0. mossambicus (1.4%) 0. marmoratus (1.3%), and M. nemurus (1 .I%). Composition and frequency of occurrence of food items iii have been studied. Phytoplankton, insects and zooplankton were found to be the main food items consumed of different fish species in the reservoir. While the least food items were mollusks, juvenile fish and crustaceans. Mystacoleocus marginatus, Cyclochelichthys apogon and Oreochromis mossambicus were largely omnivore at the time they were analyzed. While Hampala macrolepidota, Osteochilus hasseltii, Oxyleotris marmoratus and Mystus nemurus were highly carnivorous at the time they were analyzed. The phytoplankton community was composed of six different groups, (chlorophytes, cyanophytes, bacillariophytes, crysophytes, euglenoids and dinoflagellates) with a mean total density of 20.41 X lo4 cells ml-I. Among the six groups, chlorophytes was the most dominant with a mean density of 64,806.40 cells ml-I, followed by bacillariophytes (51,836.28 cells ml-I); cyanophytes (48,916.48 cells d l ) ; dinoflagellates (24,943.25 cells ml-I); crysophytes (1 1,387.68 cells ml-I) and euglenoids (2,189.59 cells ml-I). On the other hand, the zooplankton community consisted of three groups, namely, copepods, cladocerans and rotifers. Zooplankton was dominated by copepods with a total density of 2,701.27 organisms I", followed by rotifers (2,297.40 organisms I-') and cladocerans (7,16.47 organisms I-'). The macrobenthos of Semenyih Reservoir was composed of mollusks, annelids and chironomids, with a mean total density of 13,658.33 organisms/m2. Among these groups, mollusks were the most dominant with a mean density of 11,525.17 organisms/m2; followed by chironomids (1,599.88 organisms/m2) and annelids (533.29 organisms/m2). Physico-chemical and biological parameters of Semenyih Reservoir were also studied. Temperature, dissolved oxygen, secchi disk visibility and pH values range from 27.55-30.00 OC, 6.63-7.33 mg I-'; 50.60 - 99.80 cm; and 6.96 - 7.84, respectively. Nitrate-nitrogen, phosphate-phosphorous, silica and ammonia-nitrogen ranges from 0.09 mg 1-I to 0.15 mg I-', 2.71-5.26 mg I'', 0.2-0.3 mg I-' and 0.06 - 0.24 mg I-' respectively. One concluding sentence about the fish population, Semenyih Reservoir was a mesotrophic body of water.